Theologie als Topologie: Bemerkungen zum Raumkonzept von Joh 1,43-51 - Huber, Konrad (Zeitschrift für katholische Theologie, 1999)
Despite a surprising vagueness of the scene of action observations concerning the concept of space within John 1:43–51 reveal some distinct topological perspective of the narration primarily manifesting itself as a function of characterization of persons, especially of the main actors Jesus and Nathanael. In so far as this perspective is arranged and thus is to be understood in a figurative, theological sense it confirms not only the understanding of Jesus' identity gained from the Interpretation of the Son-of-Man saying in John 1:51 as a reference to Gen 28:11–19 (Jesus as place of God's presence and revelation). In regard to the view of the figure of Nathanael and its characteristic localisation "under the fig tree" (1:48,50) further conclusions can also be drawn concerning the course of belief and understanding.